Neutropenia. - Leite, F (1998)
The authors reviewed the subject of neutropenia in what concern its definition, pathophysiology, clinical features, diagnosis and principles of treatment. A new pathophysiological classification of neutropenia and an evaluation of neutropenic patients are proposed. The extent of laboratory evaluation depends greatly on the duration and severity of the neutropenia. The hematopoietic growth factors controlling the growth, development, differentiation and activation of the hematopoietic progenitor cells have revolutionized the treatment of neutropenia.